Who Was I? The Dual Role of the Researcher in the Study – “Dirty Work” in the Field by Family Probation Officers in Poland - Miśkiewicz, Katarzyna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2024)
This article aims to determine who the author was during the study. The uncertainties expressed therein include methodological and ethical challenges I encountered during a research project on the fieldwork of family probation officers in the central districts of a large city in Poland. I describe these challenges through the lens of my experiences and emotions, which accompanied me in my role as a researcher because they constituted part of the empirical material. Analytic autoethnography formed the basis to fulfil this task. The research material was derived from a several-month-long observation the work done by family probation officers. The collected data revealed that research work in the field carries with it physical, social, moral and emotional burdens. The results of the analysis lead me to conclude that while being in the field, I conducted “dirty work” and that my role was connected with the identity I assumed due to my research and the role ascribed to me by probation officers.